2016
DOI: 10.1007/s12011-016-0914-x
|View full text |Cite
|
Sign up to set email alerts
|

Association of Some Vitamins and Minerals with Periodontitis in a Nationally Representative Sample of Korean Young Adults

Abstract: The purpose of this study was to investigate whether the intakes of some kinds of vitamins and minerals are associated with periodontitis in a nationally representative sample of young adults. This study comprised 2049 young adults aged 19-39 years who took both periodontal examination and nutrition survey. The vitamin and mineral intakes were calculated from dietary intake data gained by complete one-day 24-h recall interviews, and the intake levels for each nutrient were classified by the Recommended Nutrien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 36 publications
2
39
0
1
Order By: Relevance
“…Chronic periodontitis was demonstrated to be marginally associated with a lower Vitamin A intake in young adult Korean women. 4 Low serum levels of a number of carotenoids, in particular beta-cryptoxanthin and beta-carotene, were demonstrated to be associated with an increased prevalence of periodontitis in a sample of 1258, 60-70 years old, Western European men. 5 Oral supplementation of all-trans retinoic acid every other day in a Porphyromonas gingivalis-induced periodontitis model in mice was shown to arrest periodontal inflammatory disease, inhibit inflammatory cell infiltrate, enhance T-regulatory cell activation, and arrest further alveolar bone loss.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Chronic periodontitis was demonstrated to be marginally associated with a lower Vitamin A intake in young adult Korean women. 4 Low serum levels of a number of carotenoids, in particular beta-cryptoxanthin and beta-carotene, were demonstrated to be associated with an increased prevalence of periodontitis in a sample of 1258, 60-70 years old, Western European men. 5 Oral supplementation of all-trans retinoic acid every other day in a Porphyromonas gingivalis-induced periodontitis model in mice was shown to arrest periodontal inflammatory disease, inhibit inflammatory cell infiltrate, enhance T-regulatory cell activation, and arrest further alveolar bone loss.…”
Section: Introductionmentioning
confidence: 94%
“…Investigations demonstrated a significant correlation between Vitamin A deficiency and the presence of chronic periodontitis. Chronic periodontitis was demonstrated to be marginally associated with a lower Vitamin A intake in young adult Korean women . Low serum levels of a number of carotenoids, in particular beta‐cryptoxanthin and beta‐carotene, were demonstrated to be associated with an increased prevalence of periodontitis in a sample of 1258, 60‐70 years old, Western European men .…”
Section: Introductionmentioning
confidence: 94%
“…From these 46 potential relevant articles, 31 did not meet the criteria. Finally, 15 publications (7 cross-sectional studies [23][24][25][26][27][28][29], 2 case-control studies [30,31], 2 cohort studies [32,33]), and 4 RCTs [34][35][36][37]) were selected for systematic review, as shown in the flow chart ( Figure 1). Excluding the RCTs, 6 of the remaining 11 studies estimated vitamin C intake from dietary investigation and 6 studies measured blood vitamin C concentration.…”
Section: Literature Searches and Study Characteristicsmentioning
confidence: 99%
“…With regard to exposure, 4 cross-sectional studies [23][24][25][26], one case-control study [31] and one cohort study [32] assessed dietary intake. Of these studies, five used dietary recall [23][24][25][26]31], specifically, two studies used multiple dietary recalls [24,31], and three used a single dietary recall [23,25,26]. Since a single 24-h dietary recall could not be considered to reflect one's habitual diet [38], multiple 24-h recalls are desirable and this technique was rated as "satisfactory".…”
Section: Quality Evaluationmentioning
confidence: 99%
See 1 more Smart Citation